Value-based healthcare as a trigger for improvement initiatives. Issue 4 (2nd October 2017) - Nilsson, Kerstin; Bååthe, Fredrik; Erichsen Andersson, Annette; Sandoff, Mette
Abstract : Purpose: This study explores four pilot teams' experiences of improvements resulting from the implementation of value-based healthcare (VBHC) at a Swedish University Hospital. The aim of this study is to gain a deeper understanding of VBHC when used as a management strategy to improve patients' health outcomes. Design/methodology/approach: An exploratory design was used and qualitative interviews were undertaken with 20 team members three times each, during a period of two years. The content of the interviews was qualitatively analysed. Findings: VBHC worked as a trigger for initiating improvements related to processes, measurements and patients' health outcomes. An example of improvements related to patients' health outcomes was solving the problem of patients' nausea. Improvement related to processes was developing care planning and increasing the number of contact nurses. Improvement related to measurements was increasing coverage ratio in the National Quality Registers used, and the development of a new coding system for measurements. VBHC contributed a structure for measurement and for identification of the need for improvements, but this structure on its own was not enough. To implement and sustain improvements, it is important to establish awareness of the need for improvements and to motivate changes not just among managers and clinical leaders directly involved in VBHC projects but also engage all other staff providing care. Originality/value: This study shows that although the VBHC management strategy may serve as an initiator for improvements, it is not enough for the sustainable implementation of improvement initiatives. Regardless of strategy, managers and clinical leaders need to develop increased competence in change management.